Newer insights into prostatic utricle in proximal hypospadias - Mamta Sengar; Niyaz Ahmed Khan; Yousuf Siddiqui; Anup Mohta; Alisha Gupta; Chhabi Ranu Gupta (Wolters Kluwer Medknow Publications, 2022)
Introduction: Prostatic utricles (PUs) are the remnants of Mullerian ducts found in the male posterior urethra. Enlarged symptomatic utricles are known to be associated with hypospadias. There is a dearth of literature defining an enlarged utricle and also its clinical significance. Aims: The aim of this study was to describe anatomical difference of PUs of cases with severe hypospadias and also to find their clinical significance if any. Materials and Methods: A prospective study was carried out, and all patients with proximal hypospadias were enrolled. Cystoscopy was performed in all cases. Symptomatology, size, and location of PU were recorded. PU of >0.5 cm was considered enlarged. Results: In the present series, a total of 70 cases were included over a period of 2 years. Enlarged utricle was found in 47/70 (67.14%) on cystoscopy. They were wide-mouthed and negotiated 9 Fr/11 Fr cystoscope with ease. Recurrent epididymo-orchitis, recurrent urinary tract infection, and obstructive features were the most common complications requiring intervention. Conclusions: PUs in boys with hypospadias are enlarged as well as wide-mouthed. Most of these remain asymptomatic, but few of them carry the potential of complications. Cystoscopy helps in direct visualization of utricular anatomy, so it should be a preferred investigating modality for investigating a PU.